Semantic Fields in Sign Languages. Colour, Kinship and Quantification - Zeshan, Ulrike (Sign Language Typology [SLT], 2016)
This book presents primary data and typological comparisons across sign languages with respect to three semantic fields: kinship terms, colour terms and quantification. Based on a large-scale study of 32 sign languages from all over the world, these topics are explored in 10 sign languages, accompanied by an introductory part and an appendix with original research materials.